2018
DOI: 10.1111/gfs.12363
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lactic acid bacteria strains isolated from various substrates on the fermentation quality of common vetch (Vicia sativa L.) in Tibet

Abstract: Eight lactic acid bacteria (LAB) strains isolated from five naturally fermented silages of different ensilage materials on the Tibetan Plateau were characterized, and their effects on the silage quality of common vetch (Vicia sativa L.) were studied. These LAB isolates were evaluated using morphological, physiological and biochemical tests. The eight isolated strains and one commercial inoculant (Lactobacillus plantarum MTD‐1) were subsequently added to common vetch for ensiling 60 days. All the isolated strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 33 publications
5
30
0
1
Order By: Relevance
“…As expected, the strains XM2, 265, and 867 could grow normally at pH 3.5 and the strain XM2 could grow weakly at pH 3.0, which indicates its tolerance to acidity and ability to grow in low pH environments and consistent with the Butyric acid, g kg -1 0.22 ± 0.01a 0.24 ± 0.01a 0.13 ± 0.01c 0.18 ± 0.01b 0.24 ± 0.01a LA/AA 1.02 ± 0.04b 1.12 ± 0.01b 8.87 ± 0.67a 1.40 ± 0.04b 1.42 ± 0.03b NH 3 -N, g kg -1 8.37 ± 0.14a 6.35 ± 0.14b 3.23 ± 0.17d 3.42 ± 0.06c 3.43 ± 0.08c Lactic acid bacteria, cfu g -1 5.30 ± 0.03d 6.18 ± 0.07a 6.19 ± 0.03a 5.53 ± 0.04c 6.00 ± 0.07b findings of Wang et al who found that Lactobacillus plantarum showed high tolerance to low pH (Wang et al, 2018). Besides, all the isolated strains could grow well in a wide range of temperatures from 5 to 30˚C.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…As expected, the strains XM2, 265, and 867 could grow normally at pH 3.5 and the strain XM2 could grow weakly at pH 3.0, which indicates its tolerance to acidity and ability to grow in low pH environments and consistent with the Butyric acid, g kg -1 0.22 ± 0.01a 0.24 ± 0.01a 0.13 ± 0.01c 0.18 ± 0.01b 0.24 ± 0.01a LA/AA 1.02 ± 0.04b 1.12 ± 0.01b 8.87 ± 0.67a 1.40 ± 0.04b 1.42 ± 0.03b NH 3 -N, g kg -1 8.37 ± 0.14a 6.35 ± 0.14b 3.23 ± 0.17d 3.42 ± 0.06c 3.43 ± 0.08c Lactic acid bacteria, cfu g -1 5.30 ± 0.03d 6.18 ± 0.07a 6.19 ± 0.03a 5.53 ± 0.04c 6.00 ± 0.07b findings of Wang et al who found that Lactobacillus plantarum showed high tolerance to low pH (Wang et al, 2018). Besides, all the isolated strains could grow well in a wide range of temperatures from 5 to 30˚C.…”
Section: Discussionmentioning
confidence: 82%
“…The growth situation was measured and evaluated according to the optical density (OD) value. The OD value (>1.5) was identified as “good growth”; OD value (1.0–1.5) was identified as “normal growth”; OD value (0.5–1.0) was identified as “weak growth”; OD value (< 0.5) was identified as “no growth” (Wang et al., 2018). Carbohydrate assimilation and fermentation of 49 diverse compounds with one control were identified on analytical profile index 50 carbohydrates strips by API 50 CH (BioMérieux, Marcy l’ Etoile) (Cai, Benno, et al., 1999).…”
Section: Methodsmentioning
confidence: 99%
“…The content in each silo was mixed thoroughly and sampled for analysis. Silage extract was prepared by adding 25 g of corn stalk silage to 225 mL deionized water, storing the sample for 24 h at 4 °C and then manually homogenizing the sample for 2 min according to the method described by Wang et al [24]. The pH of the water extract was measured using a pH meter (FiveEasy Benchtop pH Meter FE20, Mettler-Toledo, Columbus, OH, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The number of studies on the selection and the effect of the addition of new bacterial strains for use as silage inoculants has increased in recent years (Zhang et al 2000;Wang et al 2018;Ding et al 2019;Soundharrajan et al 2019;Amaral et al 2020;Zhao et al 2020;Guan et al 2020a). However, the biotechnological potential of LAB involved in silage fermentation remains poorly explored.…”
Section: Selection Of Micro-organisms For Ensilingmentioning
confidence: 99%
“…3). The relationship between the forage or substrate and epiphytic LAB inoculants is still unclear (Wang et al 2018). The epiphytic microbiota of the corn and sorghum plant was inoculated in oat to aid in understanding the role of microbiota during ensiling (Wang et al 2020).…”
Section: Obtaining Strainsmentioning
confidence: 99%